ISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BEASISWA MAMRE GEREJABATAK KARPROTESTAN(GBKP) DENGAN METODE TOPSIS - Miska Irani Tarigan; Yosi Latersia Sitepu (PUBLIKASI ILMIAH TEKNOLOGI INFORMASI NEUMANN (PITIN), 2016)
Scholarship is one of the program to helpease the students on paying tuition fees, but mistake is happen frequently on deciding who deserve the scholarship because it is still done manually and there is no certain criteria about which student supposed to get a scholarship To avoid the wrong decision about scholarships,there is a need of a Decision Support System.One method that can be used for decision support system is Topsis. The research is done by finding the weights for each attribute, and then made the ranking process that will determine the optimal alternative. The result of this research is more precise thanthe manual system is used for this to scholarship recipients.